The influence of firm-specific attributes on corporate social responsibility disclosure / Mohamad Norsyahizzat Ramli, Raja Adzrin Raja Ahmad and Noor Hidayah Ab Aziz - Ramli, Mohamad Norsyahizzat; Raja Ahmad, Raja Adzrin; Ab Aziz, Noor Hidayah (UiTM Cawangan Johor, 2019)
Corporate social responsibility aims to optimise the reciprocal benefits of the firm and the various stakeholders. It acts as a mechanism for firms to demonstrate their concern towards the society wellbeing. Corporate social responsibility disclosure refers to series of information pertaining to organisation to other parties in order to provide solution to improve accountability to stakeholder. In Malaysia, the disclosure for corporate social responsibility activities is still voluntary. Hence, the level of disclosure is still inconsistent. Accordingly, this paper aims examine the extent of CSR disclosure for Malaysian listed firms. In addition, it will look into the influence of firm-specific attributes towards corporate social responsibility disclosure for Malaysian listed firms namely firm size, profitability, leverage and industry type. The sample includes firms taken from the top 100 companies from the ranking produced by Minority Shareholder Watchdog Group (MSWG). Data are gathered for five consecutive years which are from 2013 to 2017 inclusive, giving a total of 150 firm-year observations. As for the items for corporate social responsibility disclosure, they are taken from the Global Reporting Initiatives (GRI) guidelines due to its comprehensiveness. Comparatively, the findings indicate that the level of corporate social responsibility disclosure is still low with a mean disclosure of 32 items out of 99 items studied. The multivariate analysis reveals that leverage, profitability and industry significantly influence the corporate social responsibility disclosure. The insights provided in this paper could be valuable especially for the purpose of generating corporate social responsibility disclosure policies and strategies.